Pengaruh Kualitas Produk, Kualitas Layanan, dan Harga Pada Minat Beli Ulang Konsumen Restoran Ayam Bang Dava - Rizal Nur Qudus, Mohamad; Sri Amelia, Nita (International Journal Administration, Business & Organization, 2022)
The purpose of this study is to determine and analyze the effect of product quality, service quality, and price on the repurchase intention of Bang Dava Chicken consumers. The research method used is descriptive quantitative with primary data obtained from distributing online questionnaires to 200 respondents, namely people who have purchased Bang Dava Chicken products at least once. The data that has been collected was analyzed using descriptive analysis and multiple regression with the help of the SPSS program. The results of this study indicate that product quality, service quality, and price have an effect of 55.8% on consumer repurchase intention of Ayam Bang Dava, while the most dominant factor influencing Bang Dava Chicken consumer repurchase intention is price.